Reliability of the university of Texas classification in predicting the outcomes of diabetic foot in a tertiary Center in Kerala: A prospective observational study - Rejana Rachel Joy; Ashok Ninan Oommen; Anuraj Appukuttan; John Thomas (Asian Journal of Medical Sciences, 2023)
Background: Diabetic foot ulcer (DFU) is one of the most serious complications of diabetes and frequently necessitates amputation, which lowers quality of life with the distressing prospect of re-amputation and increased mortality. The available classifications for a standardized approach to diabetic foot ulceration, though crucial in predicting clinical outcomes, have their limitations. Aims and Objectives: This study examined the reliability of the University of Texas (UT) classification system in predicting outcomes of diabetic foot in a tertiary center in Kerala, South India. Materials and Methods: In this prospective observational study, 98 DFU patients at Jubilee Mission Medical College and Research Institute, Thrissur, from December 2019 to June 2022 were categorized according to UT classification, and the treatment with outcomes for 6 months was recorded. Results: Among the total population, 24.4% of diabetic feet achieved healing without amputation. We observed an increasing incidence of impairment of healing (P=0.018) and in the number of amputations in Grades 1, 2, and 3 (P=0.000). At 6 months, 52% of diabetic feet, including those who underwent amputation, healed completely. Conclusion: DFU in a lower grade but higher stage according to the UT classification showed impaired healing and higher amputation rates as this system includes infection and ischemia. This classification allows reliable categorization and enables re-allocation of grade and stage of diabetic foot during treatment and follow-up, thereby facilitating effective management and predicting outcome.